Parallel Computation of Smoke Movement During a Car Park Fire - Weisenpacher, Peter; Glasa, Ján; Halada, Ladislav (Computing and Informatics, 2017)
In this paper the use of Fire Dynamics Simulator (FDS) for parallel computer simulation of the smoke movement during a fire of two passenger cars in an underground car park is investigated. The simulations were executed on a high-performance computer cluster. A specific problem of FDS parallel computation using Message-Passing Interface (MPI) is a separate solution of governing equations on computational subdomains causing a loss of accuracy. Therefore, the impact of parallelisation on simulation accuracy in the case of using a greater number of computational cores of the computer cluster is studied with the aim to increase the computational performance and enable practical application of such simulations for fire safety measures. The geometrical model and material properties of the cars used in the simulation have been verified by a full-scale fire experiment in open air. We describe the results of a series of simulations of several fire scenarios with different numbers of parked cars and ventilation configurations and determine times and locations at which conditions in the car park become untenable for human life. The simulation indicates that proper ventilation prolongs tenable conditions by several minutes.